2009
DOI: 10.1002/polb.21680
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of nano‐sized epoxy oligosiloxanes for fabrication of transparent nano hybrid materials

Abstract: Nano‐sized epoxy oligosiloxanes (EO) were prepared by condensation reaction between 3‐glycidoxypropyltrimethoxysilane (GPTS) and Diphenylsilandiol (DPSD). Through a composition change of GPTS and DPSD, EO of various structure and sizes were obtained. The molecular structure and size of EO synthesized were investigated by experimental measurements. Regardless of their composition, molecular structure of EO was linear or branch. The amount of species of high molecular weight and their molecular size increased wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 25 publications
2
9
0
Order By: Relevance
“…Particularly, propylene oxide (PO) and styrene oxide of cyclic ethers have been polymerized either by cationic catalysts or anionic catalysts, and also, more selective catalyst systems and their products have been elucidated by different spectroscopic techniques 3–8. Inoue7 and Chisholm et al8 suggested that the polymerization of PO initiated with porphyrin aluminum chloro complex proceeded as follows, with the alkoxide complex as the growing species: 3‐Glycidyloxypropyltrimethoxysilane (GPTS) is one of the most commonly used precursors for the preparation of inorganic–organic hybrid polymers, which are used, for example, for hard coatings of organic polymers, contact lens materials in the optical industry, electronics, membranes, sensors, nanoimprinting, wave guides, and biology 9–12…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, propylene oxide (PO) and styrene oxide of cyclic ethers have been polymerized either by cationic catalysts or anionic catalysts, and also, more selective catalyst systems and their products have been elucidated by different spectroscopic techniques 3–8. Inoue7 and Chisholm et al8 suggested that the polymerization of PO initiated with porphyrin aluminum chloro complex proceeded as follows, with the alkoxide complex as the growing species: 3‐Glycidyloxypropyltrimethoxysilane (GPTS) is one of the most commonly used precursors for the preparation of inorganic–organic hybrid polymers, which are used, for example, for hard coatings of organic polymers, contact lens materials in the optical industry, electronics, membranes, sensors, nanoimprinting, wave guides, and biology 9–12…”
Section: Introductionmentioning
confidence: 99%
“…In particular, organic-inorganic hybrid materials realized via a nonhydrolytic sol-gel process, where inorganic networks are formed by a condensation reaction without water, can be easily synthesized and exhibit controllable characteristics with a suitable selection of precursors and optimization of processing parameters. [12][13][14][15][16] Moreover, the absence of water molecules and hydroxyl groups in non-hydrolytic sol-gel derived materials can provide higher thermal and chemical stability relative to hydrolytic sol-gel derived materials. Exploiting these advantages, Jung et al reported high performance barrier coating layers using non-hydrolytic sol-gel synthesized hybrid materials (hybrimers).…”
mentioning
confidence: 99%
“…Figure 2b shows the 29 Si-NMR result of the EFS resin, revealing the condensation degree of siloxane bonds (SiOSi) in the organic-inorganic hybrid material. The degree of condensation was calculated by the following equation, [52] The degree of condensation…”
Section: Figure 1amentioning
confidence: 99%